Corilagin Counteracts IL-13Rα1 Signaling Pathway in Macrophages to Mitigate Schistosome Egg-Induced Hepatic Fibrosis - Li, Yi-Qing; Chen, Yun-Fei; Dang, Yi-Ping; Wang, Yao; Shang, Zhen-Zhong; Ma, Qian; Wang, Yu-Jie; Zhang, Juan; Luo, Lei; Li, Quan-Qiang; Zhao, Lei (Frontiers in Cellular and Infection Microbiology, 2017)
The IL-13Rα1 signalling pathway and M2 macrophages play crucial roles in schistosome egg-induced hepatic fibrosis via the expression of pro-fibrotic molecules. This study aims to investigate the inhibitory effect and mechanism of action of corilagin on schistosome egg-induced hepatic fibrosis via the IL-13Rα1 signalling pathway in M2 macrophages in vitro and in vivo. The mRNA and protein expression of IL-13Rα1, PPARγ, KLF4, SOCS1, STAT6, p-STAT6 and TGF-β was measured in vitro with corilagin treatment after IL-13 stimulation and in vivo corilagin treatment after effectively killing the adult schistosomes in schistosome-infected mice. Histological analysis of liver tissue was assessed for the degree of hepatic fibrosis. The results revealed that corilagin significantly reduced the expression of PPARγ, KLF4, SOCS1, p-STAT6 and TGF-β compared with model group and praziquantel administration (p<0.01 or p<0.05) in vivo and in vitro, which indicated a strong anti-fibrogenic effect of corilagin. As well, the inhibitory effect of corilagin showed a significant dose-dependence (p<0.05). The area of fibrosis and distribution of M2 macrophages in mouse liver tissue were reduced significantly and dose-dependently with corilagin treatment compared to model group or praziquantel administration (p<0.01 or p<0.05), indicating that corilagin supressed IL-13Rα1 signalling pathway and M2 macrophage polarization effectively in vivo. Furthermore, the anti-fibrogenic effect persisted even when IL-13Rα1 was up- or down-regulated in vitro. In conclusion, corilagin can suppress schistosome egg-induced hepatic fibrosis via inhibition of M2 macrophage polarization in the IL-13Rα1 signalling pathway.